1983
DOI: 10.1002/cber.19831160603
|View full text |Cite
|
Sign up to set email alerts
|

Synthesen mit 2,4‐Dimethylen‐1,3‐dithietanen. Mercaptopyridine; Thiazole; Dithiole; mesoionische und nichtmesoionische 1,2,3‐Thiadiazole

Abstract: Die aus den 2,4-Dimethylen-l,3-dithietanen 1 in situ erzeugten Thioketencarbonsaureester 6 cyclokondensieren mit Aminocrotonsaure-Derivaten 5 zu den 4-Mercaptopyridinen 4, mit Glycinbzw. Thioglycolsaureester 7 zum Alkylidenthiazolidin bzw. Alkyliden-l,3-dithiolan 8. Dagegen findet rnit Diazoalkanen 1,3-dipolare Cycloaddition statt, wobei in einem Arbeitsgang die noch nicht beschriebenen mesoionischen und nichtmesoionischen 5-Methylen-l,2,3-thiadiazole 10 bzw. 9 gebildet werden.Syntheses with 2,4-Dimethylene-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…The bonding about S1 is slightly asymmetrical ( Table 1). The remaining bond lengths and angles of ring A are in agreement with values reported for similar structures (Capuano et al, 1983).…”
Section: Commentsupporting
confidence: 90%
“…The bonding about S1 is slightly asymmetrical ( Table 1). The remaining bond lengths and angles of ring A are in agreement with values reported for similar structures (Capuano et al, 1983).…”
Section: Commentsupporting
confidence: 90%
“…Some mechanistic studies on the reaction of N ‐tosylhydrazones with S 8 have been reported . Herein, we propose a possible catalytic cycle of arylketoacylhydrazones with S 8 .…”
Section: Resultsmentioning
confidence: 96%
“…As an important heterocyclic compound, 1,2,3‐thiadiazole has been widely used in medicine, pesticides and organic synthesis due to its unique biological activity and inherent reactivity (Figure ). Traditional methods for constructing 1,2,3‐thiadiazole skeletons include the followinng four types: (a) Hurd‐Mori synthesis; (b) heterocyclization of α ‐diazo thiocarbonyl compounds (Wolff Synthesis); (c) cyclization of diazoalkanes onto a C=S (Pechmann Synthesis); and (d) other cyclization methods . However, there are some disadvantages in the above methods, such as the use of substrates that are not easily available, a narrow substrate range, and harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is widely used as a useful organic intermediate in synthetic chemical reactions . In general, the synthesis of 1,2,3‐thiadiazole mainly includes the following aspects: (a) diazotized α‐aminoketones react with Lawesson reagents; (b) the Hurd−Mori reaction; (c) the reaction of diazomethane with phenyl isothiocyanate; (d) 1,3‐dipolar cycloaddition of diazoalkanes to thiocarbonyl compounds; [3+2] cycloaddition of α‐enolic dithioesters with tosyl azide; and (f) the reaction of lithium (trimethylsilyl)diazomethane with thiocarbonyl compounds . However, these methods developed often suffer from limitations including potentially explosive materials(the diazo compounds and azide), require air‐sensitive reagents(SOCl 2 , and SCl 2 ), harsh reaction conditions, and narrow substrate scope.…”
Section: Methodsmentioning
confidence: 99%